Planejamento e Estratégia de Comunicação para a TV UFMA na transição para a TV 3.0 - Chaves, Miguel Bruno Alves; Shuen, Li-Chang (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.244403, 2024)
This paper aims to describe the planning of TV UFMA in the transition to TV 3.0, addressing the opportunities for audience interaction and the provision of personalized content. The methodology employed included a questionnaire directed at the station’s team, composed of members from the areas of management, journalism, production, technical, and engineering. The results highlight the level of knowledge and expectations of the staff regarding the new technology, identifying the main challenges and the needs for technological adaptation. The research reveals proactive preparation by TV UFMA for the next generation of digital TV, demonstrating the team’s commitment and the strategies to ensure a successful transition.